A Secondary Metabolite Secreted by Penicillium citrinum Is Able to Enhance Parastagonospora nodorum Sensitivity to Tebuconazole and Azoxystrobin - Kartashov, Maksim; Voinova, Tatiana; Shcherbakova, Larisa; Arslanova, Lenara; Chudakova, Kseniya; Dzhavakhiya, Vitaly (Frontiers in Fungal Biology, 2022)
Parastagonospora nodorum causes glume and leaf blotch of wheat, a harmful disease resulting in serious losses in grain yield. In many countries including Russia, fungicidal formulations based on triazoles and on triazoles combined with strobilurins are used to control this fungus. However, their prolonged application may promote the selection of fungicide-resistant strains of P. nodorum leading to significant attenuation or even loss of fungicidal effect. Chemosensitization of plant pathogenic fungi with natural compounds represents a promising strategy for mitigating fungicide resistance and other negative impacts of fungicides. In this work, we applied a chemosensitization approach towards P. nodorum strains non-resistant or resistant to tebuconazole or azoxystrobin using 6-demethylmevinolin (6-DMM), a metabolite of Penicillium citrinum. The resistant strains were obtained by the mutagenesis and subsequent culturing on agar media incorporated with increasing doses of Folicur® EC 250 (i.e., tebuconazole) or Quadris® SC 250 (i.e., azoxystrobin). Test strains m8-4 and kd-18, most resistant to tebuconazole and azoxystrobin, respectively, were selected for sensitization experiments. These experiments demonstrated that combining 6-DMM with Folicur® enhanced fungicidal effectiveness in vitro and in vivo in addition to attenuating the resistance of P. nodorum to tebuconazole in vitro. 6-DMM was also found to augment Quadris® efficacy towards kd-18 when applied on detached wheat leaves inoculated with this strain. Experiments on P. nodorum sensitization under greenhouse conditions included preventive (applying test compounds simultaneously with inoculation) or post-inoculation spraying of wheat seedlings with 6-DMM together with Folicur® at dose rates (DR) amounting to 10% and 20% of DR recommended for field application (RDR). Combined treatments were run in parallel with using the same DR of the fungicide and sensitizer, alone. A synergistic effect was observed in both preventive and post-inoculation treatments, when the sensitizer was co-applied with the fungicide at 10% of the RDR. In this case, disease reduction significantly exceeded the protective effect of Folicur® at 10% or 20% of the RDR, alone, and also a calculated additive effect. Collectively, our findings suggest that 6-DMM is promising as a putative component for formulations with triazole and strobilurin fungicides. Such new formulations would improve fungicide efficacy and, potentially, lower rates of fungicides needed for plant pathogen control.